2022
DOI: 10.3390/ijms232012168
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Succinate Oxidation with Mitochondrial Complex II Reactive Oxygen Species Generation in Human Prostate Cancer

Abstract: The transformation of prostatic epithelial cells to prostate cancer (PCa) has been characterized as a transition from citrate secretion to citrate oxidation, from which one would anticipate enhanced mitochondrial complex I (CI) respiratory flux. Molecular mechanisms for this transformation are attributed to declining mitochondrial zinc concentrations. The unique metabolic properties of PCa cells have become a hot research area. Several publications have provided indirect evidence based on investigations using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Using fresh prostate cancer tissue Zhang et al, 2022 have shown that advancing prostate cancer is associated with mitochondrial complex II-dependent ROS production and impaired mitochondrial complex I oxidation, which originates from insufficient suppression of mitochondrial aconitase due to Zn deficiency [ 137 ]. Nuclear factor erythroid 2-related factor 2 (NRF2) is the master regulator for oxidative stress management, and the activation of NRF2-antioxidant responsive element pathway enhances Zn efflux from cell organelles including that of mitochondria [ 138 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using fresh prostate cancer tissue Zhang et al, 2022 have shown that advancing prostate cancer is associated with mitochondrial complex II-dependent ROS production and impaired mitochondrial complex I oxidation, which originates from insufficient suppression of mitochondrial aconitase due to Zn deficiency [ 137 ]. Nuclear factor erythroid 2-related factor 2 (NRF2) is the master regulator for oxidative stress management, and the activation of NRF2-antioxidant responsive element pathway enhances Zn efflux from cell organelles including that of mitochondria [ 138 ].…”
Section: Resultsmentioning
confidence: 99%
“…When carbohydrate intake is low or during fasting, the liver produces ketone bodies such as acetoacetic acid and hydroxybutyric acid. Evidence suggests that serum pyruvate levels increase in PCa [40,41],and that pyruvate levels are linked to PCa progression and metastasis [42][43][44]. Studies have found that the activity level of acetyl-CoA transferase expressed in human breast cancer and rat liver cancer is related to the rate of tumor growth, and the level of acetoacetic acid also increases accordingly [45].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, enhanced succinate oxidation by SDH has been identified as an emergent hallmark of PCa metabolism [9][10][11] . Increased reliance on succinate in response to reduced Complex I (CI) activity is also not unique to cancer, as cell-permeable succinate has been shown to overcome CI dysfunction in models of mitochondrial disease 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The remodelling of oxidative phosphorylation (OxPhos) has recently been identified as a key characteristic of high-grade prostate cancer tissue. Specifically, these studies describe a metabolic shift from NADH-linked respiration to succinate-linked respiratory function (SLRF) 9,10 . Increased SLRF in high-grade PCa tissue is also coincident with a heightened burden of heteroplasmic mitochondrial DNA (mtDNA) mutations 11 .…”
Section: Introductionmentioning
confidence: 99%